IDENTIFIKASI FAKTOR-FAKTOR PENYEBAB PROKRASTINASI AKADEMIK SISWA: SEBUAH STUDI DESKRIPTIF PADA SISWA KELAS VIII SEKOLAH MENENGAH PERTAMA - Dimastuti, Sri; Gutji, Nelyahardi; Rahmayanty, Dinny (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to describe what internal and external factors cause academic procrastination among students at SMP Negeri 22 Jambi City. The method used in this research is a descriptive quantitative approach. The sample in this research is class VIII students for the 2023/2024 academic year with a total sample of 88 students. The sampling technique uses total sampling technique. The data collection tool used was a questionnaire containing 21 statement items, then the results obtained were analyzed using the percentage formula formula C. The results of the analysis obtained proved that internal and external factors were recognized as causes of academic procrastination of class VIII students at SMP Negeri 22 Jambi City. Internal factors within students are of medium quality with a percentage of 50.5% and external factors are of good quality with a percentage of 64%.